The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cells11152370
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial ClpXP-ClpB Family Is Enriched with RNA-Binding Protein Complexes

Abstract: In the matrix of bacteria/mitochondria/chloroplasts, Lon acts as the degradation machine for soluble proteins. In stress periods, however, proteostasis and survival depend on the strongly conserved Clp/Hsp100 family. Currently, the targets of ATP-powered unfoldases/disaggregases ClpB and ClpX and of peptidase ClpP heptameric rings are still unclear. Trapping experiments and proteome profiling in multiple organisms triggered confusion, so we analyzed the consistency of ClpP-trap targets in bacteria. We also pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(43 citation statements)
references
References 140 publications
2
41
0
Order By: Relevance
“…The targets of CLPXP proteolytic activity remain controversial, despite analyses over decades in numerous organisms with diverse technical approaches, most of which involved recombinant overexpression [49,55]. As a novel approach, we now focused on endogenous proteins in their stable interactions within three mouse tissues, trying to define potential CLPX targets based on four criteria:…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The targets of CLPXP proteolytic activity remain controversial, despite analyses over decades in numerous organisms with diverse technical approaches, most of which involved recombinant overexpression [49,55]. As a novel approach, we now focused on endogenous proteins in their stable interactions within three mouse tissues, trying to define potential CLPX targets based on four criteria:…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a close comigration with CLPX was documented for GFM1 from its monomeric size (84 kDa) to positions around 250 kDa, in addition to very strong accumulation (average 10-fold). A recent review of putative CLPXP substrates in different species concluded that the translation elongation GTPase GFM1/GFM2 orthologs are exceptionally consistent candidates [49]. Curiously, the extra-mitochondrial translation initiation complex core factor EIF3C (precursor size 106 kDa) also appeared in CLPP-null mitochondria greatly accumulated (average 5-fold) and showed comigration across the entire CLPX distribution range.…”
Section: Comigration Of Mtssu Monomeric Factors With Eral1 As Expecte...mentioning
confidence: 99%
See 3 more Smart Citations